PENGARUH KOMPETENSI GURU DAN MOTIVASI BERPRESTASI SISWA TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN PENGELOLAAN USAHA PEMASARAN KELAS X PM DI SMK NEGERI 1 KARANGANYAR TAHUN AJARAN 2015/2016 - Aga Dwi Sintha; Harini Harini; Sunarto Sunarto (Department of Economics Education, Universitas Sebelas Maret, 2018)
The objectives of this research are to investigate: (1) the simultaneous effect of the teacher’s competency and the students’ achievement motivation on the learning achievement in Marketing Business Management subject matter; (2) the effect of the teacher’s on the learning achievement in Marketing Business Management subject matter; and (3) the effect of the students’ achievement motivation on the learning achievement in Marketing Business Management subject matter of the students in Grade X PM of State Vocational High School 1 of Karanganyar in Academic Year 2015/2016.This research used the quantitative method with the associative causal approach. Its population was all of the students in Grade X PM of State Vocational High School 1 of Karanganyar. The samples of research were determined by using the total sampling technique. Its data were collected through questionnaire, documentation, observation and interview techniques. The data were analyzed by using the multiple regression analysis, F test, and t test at the significance level of 0.05.The results of research are as follows. Firstly, the teacher’s competency and the students’ achievement motivation have a simultaneously positive effect as much as 39.7% on the learning achievement in the Marketing Business Management as indicated by the value of Fab= 24.37 which was greater than that of F0.05;2;69= 3.130. Secondly, the students’ achievement motivation has a positive effect as much as 7.34% on the learning achievement in the Marketing Business Management as pointed out by the value of ta= 2.343 which was greater than that of t0.05;1;71= 1.667. Finally, the students’ achievement motivation has a positive effect as much as 32.26% on the learning achievement in the Marketing Business Management as indicated by the value of tb= 5.732 which was greater than that of t0.05; 1;71= 1.667.